2008
DOI: 10.1364/oe.16.005453
|View full text |Cite
|
Sign up to set email alerts
|

Near-field imaging of Bloch surface waves on silicon nitride one-dimensional photonic crystals

Abstract: We perform a near-field mapping of Bloch Surface Waves excited at the truncation interface of a planar silicon nitride multilayer. We directly determine the field distribution of Bloch Surface Waves along the propagation direction and normally to the surface. Furthermore, we present a direct measurement of a near-field enhancement effect under particular coupling conditions. Experimental evidence demonstrates that a approximately 10(2) near-field intensity enhancement can be realistically attained, thus confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 28 publications
1
65
0
Order By: Relevance
“…This ability has been shown to provide guiding at the surface of a terminated multilayer structure [3]. Several authors have since shown experimentally their existence [4] and characterised their properties [5,6]. Moreover, due to the confinement of the wave at the surface, their use in a sensing scheme has been predicted and demonstrated [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…This ability has been shown to provide guiding at the surface of a terminated multilayer structure [3]. Several authors have since shown experimentally their existence [4] and characterised their properties [5,6]. Moreover, due to the confinement of the wave at the surface, their use in a sensing scheme has been predicted and demonstrated [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…1,2 Although BSWs have been known for more than thirty years, they have been recently reconsidered as an alternative to surface plasmon polaritons (SPP), 3 in particular in sensing applications. [4][5][6] Until now, a number of far-field and near-field investigations have been conducted on the coupling of BSW on flat [7][8][9] and corrugated planar structures. [10][11][12] Here we demonstrate that near-infrared BSWs can be selectively prism-coupled and efficiently guided through an ultrathin polymeric ridge waveguide having thickness < λ/10 realized onto a silicon nitride multilayer.…”
mentioning
confidence: 99%
“…6), supporting Bloch surface waves (BSWs). 36 The bilayer Au film system is composed of float glass (Δ 1 = 2.31) substrate and superstrate, both of thickness 0.55 mm. The air gap between the two d m = 40 nm thick Au films is d 2 = 580 nm.…”
Section: Experimental Verification and Versatilitymentioning
confidence: 99%